Global Perspective on Nasopharyngeal Carcinoma: Clinical Features, Risk Factors, and Molecular Mechanisms - Mohd Aminudin, Mustapha; Sai Peng, Sim (apan University of Health Sciences & Japan International Cultural Exchange Foundation (JICEF), 2025)
Objective: To review current knowledge on the classification, risk factors, and genetic changes involved in NPC development. Method: Published studies from major scientific databases were reviewed to summarize key findings on NPC epidemiology, histology, EBV involvement, and genetic alterations. Conclusion: Understanding the causes and molecular features of NPC is essential for early detection and better treatment. Future work should focus on improving screening and exploring targeted therapies.